2017
DOI: 10.3389/fpls.2017.00731
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Cycling from Increased Soil Organic Carbon Contributes Both Positively and Negatively to Ecosystem Services in Wheat Agro-Ecosystems

Abstract: Soil organic carbon (SOC) is an important and manageable property of soils that impacts on multiple ecosystem services through its effect on soil processes such as nitrogen (N) cycling and soil physical properties. There is considerable interest in increasing SOC concentration in agro-ecosystems worldwide. In some agro-ecosystems, increased SOC has been found to enhance the provision of ecosystem services such as the provision of food. However, increased SOC may increase the environmental footprint of some agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 68 publications
4
32
0
2
Order By: Relevance
“…Building up SOC stock through agricultural measures (e.g., cover cropping, residue incorporation, reduced tillage) can affect soil properties, soil water retention and nutrient storage, affecting the productive capacity of soils ( Ingram et al, 2016 ; Paustian et al, 2016 ). Decomposition of SOC releases mainly N, which can increase crop yields where crop N supply is limited ( Palmer et al, 2017 ). Maintenance or build-up of SOC will require regular inputs of organic matter (OM) into the soil as the mineralization process will continually deplete the SOC over time, especially in environmental zones, where soil moisture and temperature are conducive for the mineralization process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Building up SOC stock through agricultural measures (e.g., cover cropping, residue incorporation, reduced tillage) can affect soil properties, soil water retention and nutrient storage, affecting the productive capacity of soils ( Ingram et al, 2016 ; Paustian et al, 2016 ). Decomposition of SOC releases mainly N, which can increase crop yields where crop N supply is limited ( Palmer et al, 2017 ). Maintenance or build-up of SOC will require regular inputs of organic matter (OM) into the soil as the mineralization process will continually deplete the SOC over time, especially in environmental zones, where soil moisture and temperature are conducive for the mineralization process.…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance or build-up of SOC will require regular inputs of organic matter (OM) into the soil as the mineralization process will continually deplete the SOC over time, especially in environmental zones, where soil moisture and temperature are conducive for the mineralization process. The other effects of increased SOC content are decrease in the bulk density ( Chen et al, 2017 ; Palmer et al, 2017 ; Minasny and McBratney, 2018 ) and small increase in volumetric water holding capacity ( Rawls et al, 2003 ). Due to these multiple effects, there is a great interest to quantify SOC effects in agro-ecosystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of a grazed forage crop can also enhance soil organic carbon (SOC) which provides multiple co-benefits such as accumulation and retention of N and P and other ecosystem services, except when external fertilizer applications are excessive Palmer et al, 2017). Land-based livestock integration enhances C-, N-, P-, and S-cycling (Acosta-Martínez et al, 2010;Archer and Smeins, 1991;Drinkwater et al, 1998;Soussana and Lemaire, 2014), but the impacts on carbon and nutrient accumulation remain strongly influenced by co-management factors such as N and P fertilization, tillage methods, rotation length and grazing intensity (de Faccio Carvalho et al, 2010;de Lima Wesp et al, 2016;Savian et al, 2014).…”
Section: What Do We Know?mentioning
confidence: 99%
“…Soil organic carbon changes are closely related to nitrogen (N) cycling in soil, and N losses in runoff and drainage may parallel C losses in the same pathways (Palmer et al., ). A lysimeter study in a Vertisol near Narrabri, Australia, reported that dissolved organic nitrogen (DON) constituted 40% (8.7 kg ha −1 ) of total nitrogen losses (21.6 kg ha −1 ) in deep drainage (Macdonald et al., ).…”
Section: Introductionmentioning
confidence: 99%